Obama and The End of the American Dream - Peters, Michael A. author. aut Link
IX, 119 p.
Keywords: The American Dream that crystallized around James Truslow Adams’ The Epic of America originally formulated in the early 1930s and was conditioned by a decade of complexity and contradiction, of big government projects, intensely fierce nationalism, the definition of the American way, and a distinctive collection of American iconic narratives has had the power and force to successively reshape America for every new generation. Indeed, Adam’s dream of opportunity for each according to ability or achievement shaped against the old class culture of Europe emphasizes a vision of social order in which each person can succeed despite their social origins. Barack Obama, a skillful rhetorician and intelligent politician, talks of restoring the American and has used its narrative resources to define his campaign and his policies. In a time of international and domestic crisis, of massive sovereign debt, of the failure of neoliberalism, of growing inequalities, the question is whether the American Dream and the vision of an equal education on which it rests can be revitalized.